2014
DOI: 10.1016/j.oooo.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of apigenin and kaempferol on human head and neck squamous cell carcinoma

Abstract: Objective Apigenin and kaempferol are plant flavonoids with reported chemopreventive activities. This study aimed to determine the effect of apigenin and kaempferol on cell viability in cultured cells derived from the pharynx (FaDu cell line), an oral cavity carcinoma (PCI-13 cell line), and a metastatic lymph node (PCI-15B cell line) and in explanted FaDu cells. Study Design The in vitro viability of FaDu, PCI-13, and PCI-15B cells treated with apigenin and kaempferol was determined. Tumor growth of FaDu ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Oral squamous cell carcinomas (OSCC) is the sixth most prevalent cancer worldwide [104]. In in vitro studies, kaempferol displayed antiproliferative effect on pharynx (FaDu) and oral cavity carcinoma (PCI-13) [105], human esophageal squamous carcinoma (Eca-109), and human tongue squamous carcinoma (SCC4, SCC-1483, SCC-25, SCC-QLL1) cells, prevented clone formation and cell migration and invasion, and induced substantial apoptosis [104,106,107,108]. Kaempferol also caused cell cycle arrest at G0/G1 phase and downregulated Bcl-2, MMP-2, c-Jun, and hexokinase-2 expression.…”
Section: Anticancer Properties Of Kaempferolmentioning
confidence: 99%
“…Oral squamous cell carcinomas (OSCC) is the sixth most prevalent cancer worldwide [104]. In in vitro studies, kaempferol displayed antiproliferative effect on pharynx (FaDu) and oral cavity carcinoma (PCI-13) [105], human esophageal squamous carcinoma (Eca-109), and human tongue squamous carcinoma (SCC4, SCC-1483, SCC-25, SCC-QLL1) cells, prevented clone formation and cell migration and invasion, and induced substantial apoptosis [104,106,107,108]. Kaempferol also caused cell cycle arrest at G0/G1 phase and downregulated Bcl-2, MMP-2, c-Jun, and hexokinase-2 expression.…”
Section: Anticancer Properties Of Kaempferolmentioning
confidence: 99%
“…Moreover, it suppresses invasion and metastasis and downregulates the c‐Met/p38 signaling pathway (Dang et al, ; Nepal et al, 2013). Kaempferol additionally reduces the viability, tumor growth, and tumor size in different human cancer cell lines including pharynx (FaDu cell line), metastatic lymph node (PCI‐15B cell line), oral cavity carcinoma (PCI‐13 cell line), and explanted FaDu cells (Swanson, Choi, Helton, Gairola, & Valentino, ). Other studies verified the preventive role of kaempferol against renal cell carcinoma (RCC) lines (786‐O and 769‐P cells) through multiple mechanisms such as inhibition of cell growth, induction of apoptotic cell death and cell cycle arrest, upregulation of p21 and downregulation of cyclin B1 expressions, inhibition of activation of EGFR/p38 signaling pathways, and activation of PARP cleavages (Song et al, ).…”
Section: Health Perspectivesmentioning
confidence: 99%
“…1 In recent years, more and more studies have reported that apigenin possesses a wide range of biological activities, including anti-allergic, anti-microbial, anti-inflammatory, anti-viral, and anti-tumor functions. 3,4 Apigenin showed outstanding anticancer effect on various cancers such as breast cancer, 5 prostate cancer, 6 head and neck squamous cell carcinoma, 7 and so on. Compared with other flavonoids with similar structure, apigenin has low intrinsic toxicity and differential effects in normal versus cancer cells.…”
Section: Introductionmentioning
confidence: 99%